2007
DOI: 10.1080/02786820601118406
|View full text |Cite
|
Sign up to set email alerts
|

Results from the DC-8 Inlet Characterization Experiment (DICE): Airborne Versus Surface Sampling of Mineral Dust and Sea Salt Aerosols

Abstract: During May and June of 2003 NASA conducted the DC-8 InletCharacterization Experiment (DICE). The study was undertaken to quantify the performance of three passive, solid diffuser inlets used aboard the DC-8 aircraft to sample optically effective aerosol sizes. Aerosol optical properties measured behind the University of Hawai'i (UH) and the University of New Hampshire (UNH) inlets were within 10% of the ground based measurements whereas the NASA Langley (LaRC) inlet reduced scattering values for supermicromete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
188
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(192 citation statements)
references
References 49 publications
4
188
0
Order By: Relevance
“…Moore et al (2004) performed an inlet comparison study and found the SDI to effectively pass submicrometer, as well as optically relevant coarse mode aerosol. McNaughton et al (2007) tested University of Hawai'i's SDI against ground based measurements during the DC-8 Inlet Characterization Experiment (DICE) and found that submicrometer scattering agreed within 16 %. The inlet efficiently transmits both dust and sea salt particles smaller than about 4 µm (50 % cut-off) in dry diameter.…”
Section: Inletsmentioning
confidence: 99%
“…Moore et al (2004) performed an inlet comparison study and found the SDI to effectively pass submicrometer, as well as optically relevant coarse mode aerosol. McNaughton et al (2007) tested University of Hawai'i's SDI against ground based measurements during the DC-8 Inlet Characterization Experiment (DICE) and found that submicrometer scattering agreed within 16 %. The inlet efficiently transmits both dust and sea salt particles smaller than about 4 µm (50 % cut-off) in dry diameter.…”
Section: Inletsmentioning
confidence: 99%
“…It is a modified version of the shrouded inlet used by Hawaii University on board of NASA DC-8 aircraft (McNaughton et al 2007). The sample air was taken through a 4.2-meters and 22-mm diameter stainless steel tube into the cabin.…”
Section: Airborne Instrumentation and Data Preparationmentioning
confidence: 99%
“…Instrument supersaturation was stepped between three calibrated supersaturations: ∼0.28, 0.42, and 0.57 %. Ambient aerosol was sampled using the Langley Aerosol Research Group Experiment (LARGE) aircraft inlet, which has 3-4 µm cut size (McNaughton et al, 2007). Dry particle size distributions (8.5-414 nm), which are needed for the model simulations, were measured by a Scanning Mobility Particle Sizer (SMPS).…”
Section: Application Of the Model To Sample Arctas Data Setmentioning
confidence: 99%